Ultimi approdi della Corte costituzionale in tema di gestazione per altri (ovvero, cosa accade se il diritto tradisce il fatto) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This paper aims to address the latest issues in the social parenting and surrogacy area, looking at the most recent developments of the case law of the Court of Cassazione and the Constitutional Court.
Keywords: Surrogacy; social parenting; best interest of the child; parental responsibility; adoption law